Nonparametric estimation of the survival distribution under covariate‐induced dependent truncation. Issue 4 (22nd August 2021) - Vakulenko‐Lagun, Bella; Qian, Jing; Chiou, Sy Han; Wang, Nancy; Betensky, Rebecca A.
Abstract: There is often delayed entry into observational studies, which results in left truncation. In the estimation of the distribution of time‐to‐event from left‐truncated data, standard survival analysis methods require quasi‐independence between the truncation time and event time. Incorrectly assuming quasi‐independence may lead to biased estimation. We address the problem of estimation of the survival distribution when dependence between the event time and its left truncation time is induced by shared covariates. We introduce propensity scores for truncated data and propose two inverse probability weighting methods that adjust for both truncation and dependence, if all of the shared covariates are measured. The proposed methods additionally allow for right censoring. We evaluate the proposed methods in simulations, conduct sensitivity analyses, and provide guidelines for use in practice. We illustrate our approach in application to data from a central nervous system lymphoma study. The proposed methods are implemented in the R package, depLT .